Multifokal Sekonder Extrakranial Meningioma : Olgu Sunumu - Ergün S.; Erbayat Y.; Koç C.; Gündağ Papaker M.; Yıldız P. (My University, 2023)
Meningiomas arise from arachnoid cells of the meninges and are classified as Grade I (benign), Grade II (atypical), and Grade III ( malignant) according to the WHO classification [1, 2]. Extracranial cutaneous meningiomas are rare tumors and can be divided into 2 types as primary and secondary. Primary extracranial meningiomas arise from ectopic arachnoid cells or the differential development and maturation of multipotent mesenchymal cells, whereas secondary meningiomas develop from an intracranial component associated with metastasis, seeding during surgery, or direct bone invasion of the intracranial meningiomas [1-3]. A female patient with multifocal secondary extracranial meningiomas located on the left temporoparietal and left mastoid area is presented here.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (Med); Clinical Medicine (Med)